Formal education and back pain: a review. Issue 7 (1st July 2001) - Dionne, C E; Von Korff, M; Koepsell, T D; Deyo, R A; Barlow, W E; Checkoway, H
Abstract : OBJECTIVES: To summarise the scientific evidence on the relation between educational status and measures of the frequency and the consequences of back pain and of the outcomes of interventions among back pain patients, and to outline possible mechanisms that could explain such an association if found. DESIGN: Sixty four articles published between 1966 and 2000 that documented the association of formal education with back pain were reviewed. MAIN RESULTS: Overall, the current available evidence points indirectly to a stronger association of low education with longer duration and/or higher recurrence of back pain than to an association with onset. The many reports of an association of low education with adverse consequences of back pain also suggest that the course of a back pain episode is less favourable among persons with low educational attainment. Mechanisms that could explain these associations include variations in behavioural and environmental risk factors by educational status, differences in occupational factors, compromised "health stock" among people with low education, differences in access to and utilisation of health services, and adaptation to stress. Although lower education was not associated with the outcomes of interventions in major studies, it is difficult, in light of the current limited available evidence, to draw firm conclusions on this association. CONCLUSION: Scientific evidence supports the hypothesis that less well educated people are more likely to be affected by disabling back pain. Further study of this association may help advance our understanding of back pain as well as understanding of the relation between socioeconomic status and disease as a general phenomenon.